Analysis of Muscle Activity During Shooting Motion of Korean Traditional Archers - Changsun Kim; Zhou YueZhu; Dong-Ho Park; Kihoon Kim; Wangsoo Jeong; Hye-ree Kim; Kikwang Lee; Seok-Ki Min (Korea Institute of Sport Science, 2021)
The past few decades has seen increasing kinematic studies using surface electoromyography (EMG) in archery, however there has been no such specific study in Korean traditional archery. The purpose of this study was to evaluate EMGs during archery shooting motion in Korean traditional archers. Ten men Korean traditional archers were participated, and divided into two groups according to the shooting stance; parallel stance group(PSG, n=5) and oblique stance group(OSG, n=5). The surface EMGs were measured 12 muscles during shooting motion of five events including Junbi(Set), Geogung(Set up), Manjak(Full draw), Balsi(Release), Machigi(Ending). At the result, muscle activity of posterior deltoid, trapezius, rhomboid major, latissimus dorsi, biceps brachii, forearm extensor bundle, triceps brachii, levator scapulae significantly increased at event of full draw and release, then significantly decreased again at event of ending, respectively(p<.01, p<.001). The muscle activity of erector spinae(ES) was also significantly increased at event of full draw and release(p<.01, p<.001), while no significant changes in muscles of rectus abdominis, rectus femoris(RF), gluteus maximus. As a result of comparing PSG and OSG, muscle activity of RF in OSG was higher than PSG at event of release(p<.05), it remained until event of ending(p<.05). On the other hand, the higher the tension of the bow, the higher the muscle activity of the draw arm at event of release(p<.05). These results suggest that when Korean traditional archery shooting, both side arm and back muscles are more activated than the abdomen, leg and hip muscles. The parallel stance might suppress the muscle activity of the lower extremities to twist the upper body. And the higher bowstring tension needs to increase of muscle strength in BB of draw arm.